PENGARUH MEDIA TANAM TERHADAP PERTUMBUHAN SEMAI Aquilaria malaccensis Lamk. DI PERSEMAIAN - Rinna Mamonto; Johan A. Rombang; Marthen Th. Lasut (Universitas Sam Ratulangi, 2018)
Abstract The increasing of market demand along with high selling price of agarwood encouraged people to get more production by cutting down the agarwood-producing trees. As a result, the population of gaharuproducing trees become decrease and needs to be conserved. Conservation efforts is collateral with production continuity to anticipating market demand can started from planting and cultivating. One of them is the provision of quality seeds that supported by good planting media. This research studied the effect of media on the growth of Aquilaria malaccensis Lamk.,seedlings while the planting media were soil, husk, and compost. The method was Completely Randomized Design method consisting of 6 treatments and 5 replications. Each replication consists of 1 plant, so there are 30 experimental units. Treatment is distinguished based on volume comparison of planting media, namelytreatment 1 (P1) soil, treatment 2 (P2) compost, treatment 3 (P3) husk, treatment 4 (P4) combination of soil:compost (50%: 50%), treatment 5 (P5) combination of soil: husk (50% - 50%), and treatment 6 (P6) combination of compost: husk (50%: 50%).The variables which observed were plant height, stem diameter and number of leaves. The results showed that the treatment of planting media using compost (P2) gave significant effect on the increase in height and number of leaves of Aquilaria malaccensis Lamk.,seedlings. Â Key words : Aquilaria malaccensis Lamk., seedlings, soil, compost, husk